The Role of Tata Worker’s Union in Implementation of Participative Management: The Impact of Tata Worker's Union on Participative Management Policies (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Participative leadership and management style invites input from employees on all or most company decisions. The staff is given pertinent information regarding company issues, and a majority vote determines the course of action the company will take. Participative leadership encourages collaboration.[1] Employees in some organisations can feel stifled or unheard if their attempts to contribute - based on their opinions or experience - are ignored. In participative leadership, there is a forum for these ideas to be heard. Workers union play a critical role in the success or failure of the participative management policies adopted by a company. A trade union of workers is an organization formed by workers to protect their interests, improve their working conditions, increase their productivity and solidarity etc. All trade unions have objectives or goals to achieve as stated in their constitution and each one of them employ their own strategies to achieve those objectives. These unions can be considered sub-groups that are a part of an organization and exist to specifically look after the interests of workers and contribute towards the growth of the community of which it is a part.[2]